A class-II myosin is required for growth, conidiation, cell wall integrity and pathogenicity of Magnaporthe oryzae. Issue 7 (3rd October 2017) - Guo, Min; Tan, Leyong; Nie, Xiang; Zhang, Zhengguang
ABSTRACT: In eukaryotic organisms, myosin proteins are the major ring components that are involved in cytokinesis. To date, little is known about the biologic functions of myosin proteins in Magnaporthe oryzae . In this study, insertional mutagenesis conducted in M. oryzae led to identification of Momyo2, a pathogenicity gene predicted to encode a class-II myosin protein homologous to Saccharomyces cerevisiae Myo1 . According to qRT-PCR, Momyo2 is highly expressed during early infectious stage. When this gene was disrupted, the resultant mutant isolates were attenuated in virulence on rice and barley. These were likely caused by defective mycelial growth and frequent emergence of branch hyphae and septum. The Momyo2 mutants were also defective in conidial and appressorial development, characterized by abnormal conidia and appressoria. These consequently resulted in plant tissue penetration defects that the wild type strain lacked, and mutants being less pathogenic. Cytorrhysis assay, CFW staining of appressorium and monitoring of protoplast release suggested that appressorial wall was altered, presumably affecting the level of turgor pressure within appressorium. Furthermore, impairments in conidial germination, glycogen metabolites, tolerance to exogenous stresses and scavenging of host-derived reactive oxygen species were associated with defects on appressorium mediated penetration, and therefore attenuated the virulence of Momyo2 mutants. Taken together, these results suggest that Momyo2 plays pleiotropic roles in fungal development, and is required for the full pathogenicity of M. oryzae .